Instability Mechanism and Key Control Technology of Deep Soft Rock Roadway under Long-Term Water Immersion - Wei Jing; Xu Wang; Pengwei Hao; Laiwang Jing; Weipei Xue (Advances in Civil Engineering)
More and more attention has been paid to the supporting problem of deep soft rock roadway floor with long-term water immersion in recent years. However, the existing soft rock roadway support technology rarely takes into account the influence of the immersion softening phenomenon of the roadway floor and the self-supporting structure characteristics of the surrounding rock on the stability of the surrounding rock at the same time, and the influence of the creep characteristics of rock on the deformation zone of the surrounding rock requires further research on the nature and division of the self-supporting structure of the surrounding rock. In response to the issues mentioned, based on the loading and unloading properties of the surrounding rock of the soft rock roadway, a new concept of the internal and external self-bearing structure was proposed. The fact of water-immersed mudstone softening in the soft rock roadway floor was revealed through the field practice, and the shape of the internal and external bearing structure was determined based on the in situ monitoring results. Then, the instability mechanism of the internal and external self-bearing structure of the surrounding rock was analyzed, the position of the critical control point was calculated, and the key control technology based on the method of controlling floor heave by using double-row anchor cables to control the deformation of the roadway sides was put forward. Finally, the field industrial test showed that this support technology can effectively control the deformation and failure of soft rock roadway in the case of water immersion on the floor. This work can provide a technical reference for similar roadway support designs.